PELATIHAN PENGGUNAAN APLIKASI RESERVASI SEBAGAI DIGITALISASI PENGELOLAAN KUNJUNGAN DESA WISATA KREBET - Dewi, Melany Mustika; Nurmasani, Atik; Anan, Edy (Jurnal Abdi Insani, 2025)
Krebet tourist village, located in Bantul Regency, Yogyakarta Special Region, isone of the independent tourist villages. This tourist village offers wooden batikproducts, educational tour packages, and local products. The wooden batikproducts include wayang puppets, masks, and decorative statues, made fromnatural resources around the village. Educational tour packages and localproducts are also the village's mainstays. The main problem is the lack of acompetent tourism management system. Based on this, it is necessary todevelop a digital-based visit reservation application that can assist managers inorganizing visit schedules in a more structured manner. The purpose of theapplication usage training activity is to enable managers to understand thereservation application. The activity method consists of socialization, training,and evaluation. This community engagement program involved socializationand training on a digital reservation application for managing tourist visits inKrebet Tourism Village. A total of 27 participants, consisting of Pokdarwisadministrators and members, completed stages including pre-test, applicationintroduction, demo, simulation, and post-test. Evaluation results showed asignificant improvement in understanding: 95% could explain applicationfunctions, 75% understood its benefits, and 80% recognized the administrators’roles. The training effectively enhanced Pokdarwis’ digital literacy,strengthened technology-based tourism management, and promotedprofessional service standards in managing village tourism visits. Regularmentoring on the implementation of the reservation application can beconducted to enhance the technical skills of the administrators in operating thesystem effectively.